The role of the artist in society as seen in the novels of Henry James - Middleton, D F (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1963)
Henry James (1843-1916) is a curious and, by his own choice, enigmatic figure. We have a great many dates, a few letters, and little else. James's fragment of autobiography, vast as it is; is strangely unrevealing. There is a wealth of impressions as one would expect from such a writer but precious little about the man. Henry James was chary of describing his personal feelings - so much so that some doubted his ability to have any strong emotions. His autobiography, interesting as it is, is pure observation, memories of people, places and impressions, all marvellously sensitive, but little personal feeling. Intro., p. 1.
Keywords: James, Henry, 1843-1916; Journalists as artists; Art and society; Fiction -- History and criticism -- 19th century